Comparison of Hematological, Biochemical, and Hormonal Parameters Between Fetal Sex in Different Stages of Gestation of Awassi Ewes (Indian Journal of Animal Production and Management, 2026)
The physiological adaptations of pregnant ewes are influenced by gestational stage and fetal sex, which affect hematological, biochemical, and hormonal responses. However, there is limited information regarding small ruminants in practical settings. This study aimed to evaluate how fetal sex during different gestation periods impacts selected biochemical, hematological, and hormonal parameters in pregnant ewes. The study was conducted in a sheep field in Suq Al-Shuyukh, Dhi-Qar province, Iraq, from September 2025 to February 2026. The study sampled 600 pregnant ewes (aged 2-5 years, weighing 40-50 kg). Pregnancy stage and fetal sex were determined via transabdominal ultrasonography (XF50, 3.5 MHz). The ewes were classified into three gestational stages (first, second, and third trimesters) with each stage further divided by fetal sex (male and female, n=10 each). There were significant differences (P ≤ 0.05) in hematological and biochemical parameters based on fetal sex and gestational stage in ewes. In the first trimester, ewes with male fetuses displayed higher values. In the second trimester, those with female fetuses showed significant variations in hematological parameters (RBC, HGB, MCHC, and MCH). In the third trimester, the RBC count was notably higher in ewes carrying female fetuses. Additionally, fetal sex and gestational stage influenced biochemical markers, including ALT, AST, total protein, globulin, glucose, and cholesterol. Hormonal analysis indicated that placental lactogen, cortisol, estradiol (E2), and progesterone (P4) were significantly affected by these factors. In conclusion, fetal sex and gestational stage significantly influence the hematological, biochemical, and hormonal factors in pregnant ewes, making them important for reproductive assessment and herd management.
Keywords: Herbal growth promoters; antibiotic; lymphoid organ; broiler